2012
DOI: 10.1089/jwh.2011.3113
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Health Service Utilization Among Iraq and Afghanistan Veterans with Posttraumatic Stress Disorder

Abstract: Women with PTSD had higher use than men in almost all areas, as did all veterans with comorbid PTSD and depression and comorbid PTSD and AUD, regardless of gender. Better understanding these health service use differences will allow for targeted evaluation and integrated treatment interventions in veterans with PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 31 publications
7
53
1
Order By: Relevance
“…It is surprising that our rates of current AUD (11%) and past AUD (39%) were quite low despite general high rates of comorbidity between PTSD and AUD within veterans (Erbes, Westermeyer, Engdahl, & Johnsen, 2007; Maguen, Cohen, Cohen, Madden, Bertenthal, & Seal, 2012; McDevitt-Murphy et al, 2010; Seal et al, 2011). This may reflect the ongoing bias, as discussed above, for providers to avoid referring individuals with AUD to trauma-focused treatment programs, either on their own or as part of an integrated approach to treatment of comorbidity.…”
Section: Discussionmentioning
confidence: 62%
“…It is surprising that our rates of current AUD (11%) and past AUD (39%) were quite low despite general high rates of comorbidity between PTSD and AUD within veterans (Erbes, Westermeyer, Engdahl, & Johnsen, 2007; Maguen, Cohen, Cohen, Madden, Bertenthal, & Seal, 2012; McDevitt-Murphy et al, 2010; Seal et al, 2011). This may reflect the ongoing bias, as discussed above, for providers to avoid referring individuals with AUD to trauma-focused treatment programs, either on their own or as part of an integrated approach to treatment of comorbidity.…”
Section: Discussionmentioning
confidence: 62%
“…Mental health disorder diagnoses were identified using ICD-9 or CPT codes in the MDR data. The following mental health disorder categories were identified using specific ICD-9 codes: any mental health disorder (codes 29, 30, 31); psychotic disorders (codes 295, 297, 298, 293.81, 293.82)(11, 16, 23, 25, 42–44); dementia and other organic psychosis (codes 290, 294)(11, 16); mood disorders (codes 296, 311, 300.4, 309.1, 309.0, 309.4, 301.1, 301.10, 301.12, 301.13)(7, 11, 16, 18, 23, 25, 4245); substance abuse and dependence disorders (codes 291, 292, 303, 301, 305)(7, 11, 16, 25, 42, 44, 45); anxiety disorders (codes 300 except 300.4, 308.3, 309.81)(25, 42–44), and all other mental health disorders that falls between codes 29 to 31 but not included in any of the above categories.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies suggest that among civilians, women are more likely than men to seek treatment after exposure to a traumatic event; 14,15 women veterans of OIF/OEF with PTSD also had higher use of U.S. Department of Veterans' Affairs (VA) health care than men, 17 and military women had higher rates of hospitalization for mental disorders before the wars. 18 However, at least one study of women veterans with military sexual assault and PTSD suggested that they receive fewer health care services.…”
Section: Ptsd and Predictors Of Help Seekingmentioning
confidence: 99%